PHENOTYPE-SPECIFIC DIFFERENCES IN SERUM VITAMIN D AND CALCIUM LEVELS IN PATIENTS WITH OSTEOARTHRITIS - Kurbonova Zumrad Chutbayevna; Saidrasulova Gulizebo Baxtiyorovna; Nuriddinova Shahlo Fazliddinovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
This thesis investigates phenotype-specific differences in serum vitamin D and calcium levels among patients with osteoarthritis (OA). A total of 139 patients with OA were classified into three clinical-pathogenetic phenotypes: metabolic (n=64), inflammatory (n=49), and post-traumatic (n=26). Serum calcium and vitamin D concentrations were measured using standard biochemical methods. Statistical analysis showed no significant differences in calcium levels across the groups: 1.99 ± 0.07 mmol/L (metabolic), 2.00 ± 0.08 mmol/L (inflammatory), and 1.97 ± 0.05 mmol/L (post-traumatic). In contrast, vitamin D levels differed significantly, with the highest values observed in the inflammatory phenotype (8.99 ± 1.77), followed by the metabolic phenotype (8.37 ± 1.79), and the lowest in the post-traumatic phenotype (7.69 ± 1.29). These findings suggest that vitamin D deficiency is more pronounced in post-traumatic OA and may be linked to altered joint remodeling processes after injury. The results highlight the importance of assessing vitamin D status for a better understanding of OA heterogeneity and for developing phenotype-oriented diagnostic and therapeutic approaches.